Pengaruh Berbagai Jenis Mulsa Dan Aplikasi Pupuk Npk Mutiara Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium Ascalonicum, L.) - Kadek Ayu Kristiyanti; Luh Kartini; Made Sri Yuliartini (GEMA AGRO, 2021)
The purpose of this study was to determine the effect of various types of mulch and NPK pearl fertilizer on the growth and yield of shallots (Allium ascalonicum, L.). This research is a factorial experiment with a basic design randomized block design (RBD) consisting of 2 factors, namely the first factor is the type of mulch (M) which consists of 3 levels of treatment, namely straw mulch (MJ), silver black plastic mulch (MP), and husk mulch (MS). While the second factor is NPK pearl (P) fertilizer which consists of 4 levels of treatment, namely 0 kg/ha (P0), 100 kg/ha (P1), 200 kg/ha (P2), and 300 kg/ha (P3). This research was conducted in paddy fields located in Sanding Village, Tampaksiring District, Gianyar Regency with an altitude of Â± 750 masl and this research activity was carried out from February 26 to April 26 2020. The results showed that husk mulch gave a higher fresh weight of tubers per clump, namely 69.60 g, which was not significantly different from straw mulch and silver black plastic mulch, namely 61.07 g and 56.26 g. The highest fresh weight of tubers per clump and per hectare was obtained at the NPK pearl fertilizer dosage of 300 kg/ha, namely 73.61 g and 184.03 Ku, an increase of 63.94% and 63.96% compared to the NPK pearl fertilizer dosage of 0 kg/ha namely 44.90 g and 112.24 Ku.